2013
DOI: 10.1038/onc.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Cancer driver–passenger distinction via sporadic human and dog cancer comparison: a proof-of-principle study with colorectal cancer

Abstract: Herein we report a proof of principle study illustrating a novel dog-human comparison strategy that addresses a central aim of cancer research, namely cancer driver–passenger distinction. We previously demonstrated that sporadic canine colorectal cancers (CRCs) share similar molecular pathogenesis mechanisms as their human counterparts. In this study, we compared the genome-wide copy number abnormalities between 29 human- and 10 canine sporadic CRCs. This led to the identification of 73 driver candidate genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 50 publications
(93 reference statements)
3
41
0
Order By: Relevance
“…Bioinformatic analysis indicates that whereas passenger candidate genes' functions appear to be random, driver candidate genes are significantly enriched in functions that are associated with epithelial apicobasal polarity establishment and maintenance [1]. This is consistent with the observation that loss of cell polarity is a hallmark of epithelial cancers [4, 5], and supports the notion that epithelial polarity is a tumor suppressor [4-11].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Bioinformatic analysis indicates that whereas passenger candidate genes' functions appear to be random, driver candidate genes are significantly enriched in functions that are associated with epithelial apicobasal polarity establishment and maintenance [1]. This is consistent with the observation that loss of cell polarity is a hallmark of epithelial cancers [4, 5], and supports the notion that epithelial polarity is a tumor suppressor [4-11].…”
Section: Introductionsupporting
confidence: 61%
“…Via dog-human comparative genomics and oncology studies, we have identified 73 driver candidate genes (likely cancer-causative when altered) and 38 passenger candidate genes (of which alterations are unlikely cancer-causative) for colorectal cancer [1-3]. Bioinformatic analysis indicates that whereas passenger candidate genes' functions appear to be random, driver candidate genes are significantly enriched in functions that are associated with epithelial apicobasal polarity establishment and maintenance [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a functional role for RASA3 in cancer remains to be definitively established, studies from other biological fields have shown that RASA3 can inhibit RAP1 (122), which in turn has been implicated in invasion and metastasis in various cancers (123,124). RASA3 depletion can enhance signaling by integrins (125) and MAPK (64), and the possibility that RASA3 can act as a tumor suppressor has also been recently suggested through independent cross-species cancer studies (126). Our results suggest that RASA3 may play a more complex role in cancer, as the expression of WT RASA3 inhibited cell migration and invasion in gastric cancer cell lines, whereas N-terminal Var RASA3 enhanced migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for cancers with large genomic CNAs, we can apply the dog-human comparison strategy for effective driver-passenger discrimination as described (7). Critically, as elegantly discussed in several publications (2-4), these canine cancers, which bridge a gap between traditional rodent models and human clinical trials, can significantly speed up new anticancer drug development.…”
Section: Discussionmentioning
confidence: 99%